Ergonomic risk assessment in ultrasound sonographers using inertial measurement units (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2025)
CONTEXTUALIZAÇÃO: Ultrasound sonographers experience risk factors during work that contribute to pain and disability. The prevalence of pain amidst this occupation can reach 84.9%-87.7% in the USA and Canada. An emerging technology to increase the accessibility of healthcare is telerobotic remote ultrasound. However, there have been no assessments of the ergonomic risks for telerobotic ultrasound sonographers despite important differences in set up and task demands. OBJETIVOS: To assess the ergonomic risk factors experienced by sonographers during telerobotic ultrasound exams. MÉTODOS: Two sonographers were assessed during 40 ultrasound exams over 60 days, under the ethics approval (Bio 5002). Before the first session, they filled out QuickDASH questionnaire. For each data collection session they were equipped with 10 IMUs to record upper body movement. Videos were also recorded and analysed by one rater using 3 ergonomic risk questionnaires (HARM (Hand Arm Risk Assessment Method), RULA (Rapid Upper Limbs Assessment) and REBA (Rapid Entire Body Assessment)). Outcomes were analyzed descriptively. RESULTADOS: Varying degrees of postural exposures (arm elevation, axial rotation, elbow flexion, and wrist deviation) were present during telerobotic ultrasound scanning. Amongst the anatomical regions analysed, the biggest difference between sides was during ulnar deviation, with the right hand using more ulnar deviation than the left side (90th percentile: 17.6° vs 8.0°). For the elbows, both sides showed similar flexion in the lowest risk range for elbow disorders. Humeral elevation presented as a moderate risk factor for injury for both sides (90th percentile: 63.5 and 61.6). Analysis with the ergonomic risk questionnaires is ongoing. CONCLUSÕES: Humeral elevation and wrist deviation postural exposures may be risk factors for injury during telerobotic ultrasound scanning, indicating possible areas to lower the injury risk. More complete ergonomic analyses are underway to determine the risk level for telerobotic ultrasound sonographers. This study is a  novelty for using IMUs to assess the risks on telerobotic ultrasound exams and showing promising results that will be further analysed and compared with traditional ultrasound exams. IMPLICAÇÕES: The IMU showed to be a reliable asset to assess the musculoskeletal risks amidst the working place of telerobotic ultrasound, and especially in a hand-task with fast or subtle movements. Clinically, this study contributes to professionals that work with assessments either on clinics or workplace environments to enhance their outcomes with this type of equipment.